Case Report: Evidences of myasthenia and cerebellar atrophy in a chinese patient with novel compound heterozygous MSTO1 variants - Liu, Liqun; Su, Ruiting; Huang, Peng; Li, Xingfang; Xiong, Jie; Xiao, Yangyang; Mao, Dingan; Liu, Lingjuan (Frontiers in Genetics, 2022)
Misato Mitochondrial Distribution and Morphology Regulator 1 (MSTO1) is a soluble cytoplasmic protein that regulates mitochondrial dynamics by promoting mitochondrial fusion. Mutations in the MSTO1 gene cause a rare disease characterized by early-onset myopathy and cerebellar ataxia, with almost 30 cases reported worldwide. Here we reported a case of a 3-year-old boy with a novel heterozygous mutation of the MSTO1 gene (c.1A>G (p.M1?) and c.727G>C (p.A243P)). Sequencing data and subsequent validation showed that the two variants were inherited from the mother and father of the submitter (both were heterozygous). The clinical features were infancy-onset mental and motor retardation, language disorder, dysarthria, scoliosis, cerebellar atrophy, tremor, lower-extremity muscle weakness, elevated muscle enzymes, extensive myopathy with chronic atrophy, hyperventilation lungs, and previously unreported hairy back and enlarged gastrocnemius. Finally, a novel mutation site was discovered in this case, which expanded the gene spectrum and clinical phenotype of this type of disease, and provided a new direction for future treatment and research. Then we summarized the mutational spectrum, pathological, clinical features and imaging of MSTO1 mutations in a cohort of reported 30 patients and discussing the pathogenesis of MSTO1 in human.